2022
DOI: 10.1002/gps.5865
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of sleep disturbances across stages of cognitive decline

Abstract: Objectives:The purpose of this study was to investigate insomnia symptoms and excessive sleep/sluggishness across stages of cognitive decline (cognitively normal [CN], Cognitively Impairment, Not Demented [CIND], dementia) in a large, racially/ethnically diverse sample of older adults (70+) in the US. We also examined whether sleep disturbances at baseline predicted conversion to CIND or dementia at follow-up. Methods: In this secondary analysis of the Aging, Demographics, and Memory Study (ADAMS) supplement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 76 publications
1
1
0
Order By: Relevance
“…Sleep disturbances differentially impacted survival time depending on cognitive status, wherein there was a greater negative impact among participants with MoCA scores between 24-27, a range that captures normal cognition and the cusp of mild cognitive impairment. Previous research has found that the presence of insomnia symptoms at baseline (similar to our study’s “visit #1”) predicted conversion from cognitively normal to cognitively impaired, not demented (CIND, 33 and MCIover time, but not from MCI to dementia. While these previous studies did not examine the impact of sleep disturbances on mortality, there are interesting parallels with worse outcomes associated with higher cognitive status (normal cognition or MCI).…”
Section: Discussionsupporting
confidence: 75%
“…Sleep disturbances differentially impacted survival time depending on cognitive status, wherein there was a greater negative impact among participants with MoCA scores between 24-27, a range that captures normal cognition and the cusp of mild cognitive impairment. Previous research has found that the presence of insomnia symptoms at baseline (similar to our study’s “visit #1”) predicted conversion from cognitively normal to cognitively impaired, not demented (CIND, 33 and MCIover time, but not from MCI to dementia. While these previous studies did not examine the impact of sleep disturbances on mortality, there are interesting parallels with worse outcomes associated with higher cognitive status (normal cognition or MCI).…”
Section: Discussionsupporting
confidence: 75%
“…As detailed in our recent paper examining patterns of sleep disturbances across stages of cognitive decline, 30 ADAMS participants were a subset of the 1770 HRS respondents aged ≥70 from the 2000 and 2002 waves of HRS data collection. Sampling strategy for ADAMS participants included ensuring there were sufficient participants from each cognitive stratum, ranging from ‘low functioning’ to ‘high normal’ (which was determined by a self‐ or proxy‐cognitive assessment measure in the parent HRS study), and oversampling Hispanic and Black participants to achieve a nationally representative racial/ethnic sample of older adults 31 .…”
Section: Methodsmentioning
confidence: 99%